2012
DOI: 10.1038/nrn3165
|View full text |Cite
|
Sign up to set email alerts
|

Direction selectivity in the retina: symmetry and asymmetry in structure and function

Abstract: Visual information is processed in the retina to a remarkable degree before it is transmitted to higher visual centres. Several types of retinal ganglion cells (the output neurons of the retina) respond preferentially to image motion in a particular direction, and each type of direction-selective ganglion cell (DSGC) is comprised of multiple subtypes with different preferred directions. The direction selectivity of the cells is generated by diverse mechanisms operating within microcircuits that rely on indepen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
302
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 290 publications
(323 citation statements)
references
References 130 publications
20
302
0
1
Order By: Relevance
“…Physiological studies have revealed the existence of four ooDSGC subsets, responsive to upward, downward, nasal, and temporal motion (31). These subsets are morphologically similar but molecularly distinct: cdh6 is expressed primarily by ooDSGCs selective for vertical motion, whereas ooDSGCs sensitive to temporal motion express MMP17 (22).…”
Section: Resultsmentioning
confidence: 99%
“…Physiological studies have revealed the existence of four ooDSGC subsets, responsive to upward, downward, nasal, and temporal motion (31). These subsets are morphologically similar but molecularly distinct: cdh6 is expressed primarily by ooDSGCs selective for vertical motion, whereas ooDSGCs sensitive to temporal motion express MMP17 (22).…”
Section: Resultsmentioning
confidence: 99%
“…These are distinguishable from On-DSGCs in several ways: (1) their dendrites are bistratified rather than monostratified; (2) they respond to both light increments and decrements; (3) they prefer higher velocity visual stimuli; and (4) on average they have smaller dendritic and receptive fields than On-DSGCs (Barlow and Hill, 1963;Barlow and Hill, 1964;Weng et al, 2005;Rivlin-Etzion et al, 2011). On-Off DSGCs encode direction along one of the four cardinal axes: (1) upward; (2) downward; (3) forward; or (4) backward (Borst and Euler, 2011;Vaney et al, 2012). In both rabbits and mice, On-Off DSGCs project to the dorsal lateral geniculate nucleus (dLGN) and superior colliculus (SC), visual targets associated with spatial vision and reorientation of gaze, respectively (Pu and Amthor, 1990;Huberman et al, 2009;Kay et al, 2011;Rivlin-Etzion et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Combined with the centrifugal tuning of SACs (Euler et al 2002), this asymmetric wiring should, in theory, be sufficient to confer direction selectivity on the RGC ( Fig. 7C; Demb 2007;Vaney et al 2012). Rather, asymmetric wiring from SACs alone is sufficient to generate direction-selective responses in both ON DSGCs and ON-OFF direction-selective ganglion cells (Yonehara et al 2013;Park et al 2014).…”
Section: Visualizing the Functional Properties Of Identified Drosophimentioning
confidence: 99%